Pengaruh Rekrutmen Dan Pelatihan Terhadap Kinerja Karyawan Divisi Field Collection Pada PT Adira Dinamika Multi Finance Tbk Cabang - Anggana, Nizam; Yuda Alhabsy, Muhammad (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Abstrak. This study aims to determine the effect of recruitment and training on the performance of field collection division employees at PT. Adira Dinamika Multi Finance Tbk. Tebet Branch. The research method used is the Quantitative method. The population in this study was 56 field collection division employees at PT. Adira Dinamika Multi Finance Tbk. Tebet Branch with a sample size of 56 respondents using saturated sampling techniques. Data collection techniques using questionnaires. Data analysis methods using simple and multiple linear regression tests, correlation coefficients, determination coefficients, partial t tests and simultaneous f tests. The results of this study indicate that: There is an effect of recruitment on the performance of field collection division employees at PT. Adira Dinamika Multi Finance Tbk. Tebet, this can be proven from the simple linear regression equation Y = 6.636 + 0.846X1. The correlation value is 0.819. The determination coefficient value of R Square is 67%. The t-count value is 10.472 > t-table 2.005 with a significance of 0.000 < 0.05. There is an effect of training on the performance of field collection division employees at PT. Adira Dinamika Multi Finance Tbk. Tebet Branch, this can be proven from the simple linear regression equation Y = 5.370 + 0.883X2. The correlation value is 0.774. The coefficient of determination R Square is 59.9%. The t-count value is 8.976 > t-table 2.005 with a significance of 0.000 < 0.05. Simultaneously, there is an effect of recruitment and training on employee performance at PT. Adira Dinamika Multi Finance Tbk. Tebet Branch, this can be proven from the multiple linear regression equation Y = 2.815 + 0.565X1 + 0.404X2,. The correlation value is 0.850. The coefficient of determination R Square is 72.2%. The f-count value is 68.725 > f-table 3.17 with a significance level of 0.000 < 0.05 Keywords: Recruitment, Training, Employee Performance